The Asia-Pacific Region(APAC)’s AI Technology Proliferation and Cybersecurity Cooperation Strategies - 이원태; 곽진 (Journal of Platform Technology, 2024)
This study analyzes the rapid proliferation of AI technology in the Asia-Pacific region, the consequent increase in cybersecurity threats, and global big tech companies' cybersecurity cooperation strategies. The research examines the current status and factors of AI technology adoption in APAC and investigates how US-China digital hegemony competition affects APAC's digital industry ecosystem. It also analyzes the characteristics of rapidly increasing cyber threats in the region, focusing on ransomware, AI-based attacks, and state-sponsored hacking. The study finds that cybersecurity in APAC requires public-private partnerships beyond government-led political and diplomatic security alliances, with participation from global tech companies like Microsoft being essential. Based on the analysis, this study proposes five strategic tasks for global big tech companies to strengthen cybersecurity cooperation in APAC: 1) accelerating public-private partnerships, 2) enhancing threat intelligence sharing systems, 3) building open cooperation communities, 4) considering each country's legal and institutional specifics, and 5) strengthening technical and knowledge cooperation to address cybersecurity capability gaps.
Keywords: APAC; Artificial Intelligence(AI); Cyber Threat; Cybersecurity; Cybersecurity Cooperation